Acquired Methemoglobinemia from Local Anesthetics Used for Airways: Incidence, Risk Factors, and Management - Maher Ahmed Hamad Al Sultan; Shaker Ahmed Abdullah Al Faraj; Omar Adel Omar Alsubaie; Abdullah Shafi Rajeh Alshehri; Bayan Mansour Hamad Almansour; Bashayer Sulaiman Rubayyi Alshammari; Norah Adel Abdulaziz Al Jaber; Zahra Ali Alhazza (International Journal of Medical Toxicology and Legal Medicine, 2025)
Background: Acquired methemoglobinemia from topical/local anesthetics used for airway procedures is uncommon but clinically important. Risk appears highest with benzocaine sprays during transesophageal echocardiography (TEE) or bronchoscopy, whereas standard-dose lidocaine typically yields only minor, asymptomatic methemoglobin (MetHb) changes. Methods: We systematically searched PubMed (to June 2025), screened records in duplicate, and included observational clinical trials or cohort/case-control studies evaluating airway topical/local anesthetics and methemoglobinemia. Data were extracted in duplicate and synthesized narratively without meta-analysis due to heterogeneity in designs, exposures, and outcome definitions. Results: Nine observational studies met eligibility (0 randomized trials). Across mixed procedure cohorts, incidence was low (0.035% overall; 33/94,694 procedures), with higher procedure-specific rates for TEE (0.250%) and bronchoscopy (0.160). A large TEE program reported benzocaine-associated incidence 0.067% (95% CI 0.040-0.100). Inpatient status markedly increased risk (13.7 vs 0.14 per 10,000 for inpatients vs outpatients). Prospective studies of lidocaine topicalization/infiltration showed trivial mean MetHb shifts (e.g., =0.5% to 0.6%) without clinical toxicity. Conclusions: Airway topical/local anesthetic-associated methemoglobinemia is rare and concentrated around benzocaine spray in medically complex inpatients. Routine lidocaine use at standard doses demonstrated minimal clinical risk. Early recognition with co-oximetry and timely methylene blue remain central to excellent outcomes, and risk can be minimized through agent selection and dosing discipline.